Имидж рекламных персонажей - Коханенко А. И. (Журналистика и реклама, 2004)
Экземпляры: СЭ (20050811) / Инвентарный номер: 1053367 / Цена: 73.50 / Сис.шифр: 76 / Авт.знак: К 75 / ГРНТИ: 19 / ББК: 76.006